Economic Empowerment and Entrepreneurial Strategies of Women-Headed Households through Cricket Farming in Desa Wonorejo Blitar - Fitrianatsany, Fitrianatsany; Priantilianingtiasari, Ruly (Universitas Wijaya Kusuma Surabaya, 2026)
This study explores the economic empowerment and entrepreneurial strategies of female heads of households in Wonorejo Village, Blitar, through cricket farming. Using a qualitative approach, it examines how women navigate economic constraints, gender norms, and social expectations to sustain their families. Guided by Naila Kabeer’s empowerment framework, Joan Acker’s gender theory, and Moser’s indicators of economic agency, the research analyzes women’s access to resources, decision-making power, and social recognition. Findings reveal that women face multidimensional challenges, including limited capital, market access, labor demands, and social stigma. Nevertheless, engagement in cricket farming fosters adaptive strategies such as income diversification, financial prioritization, and social networking that enhance household welfare and promote agency. The study also highlights gradual shifts in gender roles, with women emerging as key economic decision-makers and local agents of social change. The research concludes that sustainable empowerment requires both practical entrepreneurial support and structural interventions, including microfinance access, technical training, and market development. Cricket farming thus functions as a vehicle for livelihood, social negotiation, and gender transformation in rural patriarchal contexts